2008
DOI: 10.1007/s11267-008-9181-y
|View full text |Cite
|
Sign up to set email alerts
|

Fluxes and Loading of Heavy Metals, Benzo[a]pyrene and Oil Products in Vilnius City

Abstract: The concentrations of heavy metals Pb, Cd, Cu, Zn and Hg, benzo[a]pyrene and oil products (C 15 -C 28 ) in bulk (wet and dry) atmospheric deposition in Vilnius city in 2005-2006 were analysed. The highest flux to the ground surface of the city residential area, reaching 1,680 mg m −2 year −1 , was determined for oil products, which in atmospheric bulk deposition was estimated to be mainly in the form of solid sediments. Among heavy metals, the highest flux was determined for Zn (113.5 mg m −2 year −1 ), while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
1
7
1
Order By: Relevance
“…The observed similarity with the order of mass concentrations calculated for trace metal accumulation on the ground surface of a residential site in Vilnius in the work by Milukaitė et al (2008) suggests that atmospheric deposition played a leading role in the pollutant build-up on the investigated surfaces. Therefore, atmospheric deposition was assumed to be a significant source of trace metal pollution for the area of Vingio Park.…”
Section: Analysis Of Urban Storm Water Runoff Chemistrysupporting
confidence: 75%
See 2 more Smart Citations
“…The observed similarity with the order of mass concentrations calculated for trace metal accumulation on the ground surface of a residential site in Vilnius in the work by Milukaitė et al (2008) suggests that atmospheric deposition played a leading role in the pollutant build-up on the investigated surfaces. Therefore, atmospheric deposition was assumed to be a significant source of trace metal pollution for the area of Vingio Park.…”
Section: Analysis Of Urban Storm Water Runoff Chemistrysupporting
confidence: 75%
“…in 2000, road transport was the largest source (97%) of the emissions into the atmosphere generated by mobile pollution sources in Lithuania (Baltrėnas et al 2004). in addition, Milukaitė et al (2008) have observed a close relationship between Cd, Cu, Pb, Zn and oil products in atmospheric deposition, suggesting that traffic represents the major source of pollution that can affect the chemical composition of atmospheric depositions in Vilnius. in addition, Milukaitė et al (2008) have observed a close relationship between Cd, Cu, Pb, Zn and oil products in atmospheric deposition, suggesting that traffic represents the major source of pollution that can affect the chemical composition of atmospheric depositions in Vilnius.…”
Section: Sampling Sitesmentioning
confidence: 92%
See 1 more Smart Citation
“…focus on urban areas is understandable, because of their high heavy metal fluxes (Milukaitė et al 2008). Elevated contents of harmful chemical elements in topsoil of the country also often have been explained by anthropogenic reasons (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The methods of determination and quality control for B(a)P and oil products were described by Milukaite et al (2008). The average hardness of control water was approximately 284 mg/l as CaCO 3 , pH ranged from 7.6 to 7.8.…”
Section: Physical Chemical Analysis Of Rww and Twwmentioning
confidence: 99%